Early effect of the fear of terrorism on a hospital's emergency department use and on the incidence of cardiovascular events: A Turkish multicenter study - AKDENİZ, ESRA (John Wiley and Sons Ltd, 2019)
Background: To our knowledge, the early effect of the fear caused by terrorism on human health, especially its effect on the number of visits to medical emergency departments (EDs), has not yet been studied. Objectives: To observe the effect of fear from terrorist alerts on the use of EDs and on the rate of cardiovascular (CV) and/or cerebrovascular events. Setting: In Istanbul, Turkey, there was a terror alert on the weekend of 19 and 20 March 2016. In this multicenter retrospective study, we compared the data of patients from that weekend with those from the preceding and following weekends. Patients: A total of 12 324 adult patients' records were included in this study: 4562 patients in the first weekend, 3627 patients in the second, terror alert weekend, and 4135 patients in the third weekend. Measurements: The ED, CV, and cerebrovascular incidence rates of the above three groups were compared. Results: The rate of ED use was the least in the weekend of the terror alert; the highest rate occurred during the weekend prior to it (female applications decreased more [P = 0.03]). The medical center that was the farthest from the crowded central places of the city and from the place where suicide bombing occurred was less affected by the decrease in use. Conclusions: Fear associated with terrorism may affect human health indirectly by preventing patients from reaching the necessary emergency healthcare facilities. This finding may be a pathfinder to decision-makers in such extraordinary emergency conditions. Further studies are needed in this field. © 2019 John Wiley & Sons, Ltd.
Keywords: cardiovascular events; cerebrovascular events; emergency department; terrorism; Turkey